Is There Civic Groups Participation in Budget Planning? A Study Budget Planning in Malang City, Indonesia - SALAHUDIN, SALAHUDIN; JAINURI, JAINURI; NURMANDI, ACHMAD (Jurnal Studi Pemerintahan, 2017)
This article aims to explore the relationship between local government and civic groups in the budget planning of the local government of Malang in Indonesia. A qualitative method are applied in this study. The findings indicate that; firstly, there isa relationship between local government and civic groups showingthat the principles of democracy (equality, participation, and justice) remain insuffi- cient in the budget planning. Secondly, the local government has dominated civic groups in the process of approval of the budget planning.These findings contribute to developing budget planning in Malang to find a way to establish democratic budget policy and to establish budget policy regarding public needs and preferences. Therefore, the local government should realize that public par- ticipation is a way to achieve democratic budget policy. On the other side, civic groups may need tobuild civic awareness and a willingness to participate in the budget policy, through civic education.